A study on determinants of household debt in Malaysia / Fatin Nurhaziqah Mat Isa - Mat Isa, Fatin Nurhaziqah (Faculty of Business and Management, 2020)
Household debt in Malaysia has always being the popular issue as it keep raising and will give impact towards the stability of economic growth. This study is conducted to determine the relationship between independent variables and dependent variables which independent variables consist of Gross Domestic Product (GDP), Housing Price Index (HPI), Interest Rate (IR), Unemployment Rate (UR) and Inflation Rate (IFR). This study is using time series analysis which data collected from period of Quarter One 2000 until Quarter Four 2018 and covers for Malaysia only. The quarterly time series data were obtained from Thomson Reuters Data Stream, Bank Negara Malaysia and World Bank Data. In order to obtain the empirical result, Multiple Linear Regression model is applied to obtain the relationship between independent and dependent variables. By using Multiple Linear Regression model, the result concludes that Housing Price Index (HPI), Interest Rate (IR) and Unemployment Rate (UR) has statistically significant impact towards the level of household debt in Malaysia with positive correlation except for Interest Rate (IR) with negative relationship. However, Gross Domestic Product (GDP) and Inflation Rate (IFR) were found to have insignificant relationship between household debts with negative correlations. Based on the results obtained, recommendations are made for the significant of study to help them in improving the household debt level in the long run.